ChemInform Abstract: Pd‐Catalyzed Desulfitative and Denitrogenative Suzuki‐Type Reaction of Arylsulfonyl Hydrazides. Issue 32 (August 2015) - Zhong, Shuangling; Sun, Chenggang; Dou, Sen; Liu, Wencong
Abstract The utility of the scalable method is demonstrated by the one‐pot two‐step coupling of bromophenylsulfonohydrazides in order to prepare terphenyl derivatives such as (VIII).